Role of hypoxia on increased blood pressure in patients with obstructive sleep apnoea. Issue 1 (January 1995) - Okabe, S; Hida, W; Kikuchi, Y; Taguchi, O; Ogawa, H; Mizusawa, A; Miki, H; Shirato, K
Abstract : BACKGROUND–Cyclical changes in systemic blood pressure occur during apnoeic episodes in patients with obstructive sleep apnoea (OSA). Although several factors including arterial hypoxaemia, intrathoracic pressure changes, and disruption of sleep architecture have been reported to be responsible for these changes in blood pressure, the relative importance of each factor remains unclear. This study assessed the role of hypoxaemia on the increase in blood pressure during apnoeic episodes. METHODS–The blood pressure in apnoeic episodes during sleep and the blood pressure response to isocapnic intermittent hypoxia whilst awake were measured in 10 men with OSA. While asleep the blood pressure was measured non-invasively using a Finapres blood pressure monitor with polysomnography. The response of the blood pressure to hypoxia whilst awake was also measured while the subjects intermittently breathed a hypoxic (5% or 7% oxygen) gas mixture. Each hypoxic gas exposure was continued until a nadir arterial oxygen saturation (nSaO2) of less than 75% was reached, or for a period of 100 seconds. The exposure was repeated five times in succession with five interposed breaths of room air in each run. RESULTS–The mean (SD) increase in blood pressure (delta MBP) during apnoeic episodes was 42.1 (17.3) mm Hg during rapid eye movement (REM) sleep and 31.9 (12.5) mm Hg during non-REM sleep. The delta MBP during apnoeic episodes showed a correlation with the decrease of nSaO2 (delta SaO2) (r2 = 0.30). The change in blood pressure in response to intermittent hypoxia whilst awake was cyclical and qualitatively similar to that during apnoeic episodes. Averaged delta MBP at an SaO2 of 7% and 5% oxygen was 12.6 (5.7) and 13.4 (3.6) mm Hg, respectively, whereas the averaged delta MBP at the same delta SaO2 during apnoeic episodes was 38.4 (15.5) and 45.2 (20.5) mm Hg, respectively. CONCLUSIONS–The blood pressure response to desaturation whilst awake was about one third of that during apnoeic episodes. These results suggest that factors other than hypoxia may play an important part in raising the blood pressure during obstructive sleep apnoea.